The effect of profitability on firm value at PT Lippo Karawaci Tbk - Hestu Nugroho Warasto; Ibnu Sina; Justika Pradyasari (Jurnal Ad'ministrare, 2022)
This study aims to determine how much influence profitability has on firm value at PT Lippo Karawaci Tbk for the period 2006 to 2020. The object in this study is PT Lippo Karawaci for the period 2006 to 2020. The type of data used in this study is secondary data obtained from financial statements. Annual PT Lippo Karawaci Tbk Period 2006 to 2020 obtained through IDX and the PT Lippo Karawaci Tbk website. This research method uses descriptive quantitative method. The data analysis technique used is descriptive statistics and linear regression analysis. The results showed that Profitability (X1) had a positive effect on Firm Value (Y) with the regression equation Y = 1.312 + 0.050X2. The correlation coefficient value is 0.390 with a determination of 15.2%.